Coached red-handed - Laurie, Victoria (Laurie, Victoria. Cat & Gilley Life coach mysteries, 2023)
Life coach Cat Cooper and her best friend Gilley can't wait to take a long vacation from low-key East Hampton. There's just one more item left on their planning checklist: stopping a killer... With Gilley heartbroken over the collapse of his marriage, Cat has the perfect remedy -- a long getaway to Italy. But before the duo can pack their bags, they first must help a troubled client carve out a fresh start of her own. Wealthy Scarlet Rubi desperately seeks a greater purpose and immediate distance from her toxic descendants. The urgency of the situation isn't quite so clear until Scarlet takes healthy steps toward progress, only to turn up dead. As Cat and Gilley investigate a slew of sketchy alibis and concrete motives from the corrupt Rubi clan while preparing to leave the East End for Europe, they soon realize the question isn't who had a deadly vendetta against Scarlet -- it's who didn't? --